(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
In the article, the relevance of teaching natural sciences, the methodical system of developing the creative abilities of students on the example of natural sciences, the development of the qualities and thinking of students today, such as creative thinking, conscious attitude to the surrounding reality, involvement and social activity, high spirituality It is thought that the development of a well-rounded person as an important factor in raising a healthy generation creates the need to use advanced pedagogical and innovative technologies on a large scale starting from the primary education system.